2018
DOI: 10.1098/rstb.2017.0322
|View full text |Cite
|
Sign up to set email alerts
|

The first digestive movements in the embryo are mediated by mechanosensitive smooth muscle calcium waves

Abstract: Peristalsis enables transport of the food bolus in the gut. Here, I show by dynamic ex-vivo intra-cellular calcium imaging on living embryonic gut transverse sections that the most primitive form of peristalsis that occurs in the embryo is the result of inter-cellular, gapjunction dependent calcium waves that propagate in the circular smooth muscle layer. I show that the embryonic gut is an intrinsically mechanosensitive organ, as the slightest externally applied mechanical stimulus triggers contractile waves.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…We previously demonstrated that early stage guts (E7–E9) are intrinsically mechanosensitive: when mechanical pressure is applied to the gut locally by pinching, it triggers two outgoing CC waves that propagate away from the point of compression (Chevalier, ). We investigate here the development of this reflex response on duodenal segments at the TTX‐insensitive and TTX‐sensitive stages E12 and E16, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that early stage guts (E7–E9) are intrinsically mechanosensitive: when mechanical pressure is applied to the gut locally by pinching, it triggers two outgoing CC waves that propagate away from the point of compression (Chevalier, ). We investigate here the development of this reflex response on duodenal segments at the TTX‐insensitive and TTX‐sensitive stages E12 and E16, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…). We have previously demonstrated by direct calcium imaging that spontaneously generated, intercellular, gap‐junction‐dependent circular smooth muscle calcium waves underpin this early motility pattern (Chevalier, ). Contractions at stage E5–E6 propagate rapidly (100–1000 μm/s), leading to apparent, immediate whole‐gut contractions (Chevalier et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this, we cultured whole intestinal explants from E9, prior to outer smooth muscle differentiation and alignment, for 72 h while decreasing or increasing circumferential muscle contraction frequency. We took advantage of the fact that fetal smooth muscle contraction depends on the activity of L-type calcium channels and myosin light chain kinase (MLCK), with calcium transients propagated between the cells via gap junctions to generate the contractile waves (Chevalier, 2018;Schultz et al, 2003). Consistent with our hypothesis, preventing these contractions during formation of the outer layer with nifedipine (a calcium channel inhibitor), ML-7 (an MLCK inhibitor), or carbenoxolone (a gap junction inhibitor) inhibited alignment of the outer muscle layer, whereas increasing the contractile frequency using the L-type calcium channel activator (S)-(-)-BayK8644 enhanced alignment (Figures 5A, S6B, and S6E; Video S3).…”
Section: Cyclic Contractions Of the Circumferential Layer Align The Omentioning
confidence: 99%
“…cortical folding constrained by skull, lung branching), as covered by Jaslove & Nelson [26] and Garcia et al [15]. Then there are the forces ( pre-stresses) that are inherently within tissues and structures, which may change over development and may direct aspects of it, as covered by Chevalier [23] in this issue, and others [20,42]. At the cell-, rather than tissue-, level, mechanical forces can affect aspects such as cell shape, organization and orientation, as described by Tetley & Mao [28] and Bagnat et al [12].…”
Section: Introductionmentioning
confidence: 99%